OPTIMASI PARAMETER KOMPOSISI KOMPOSIT SERAT KACA - KARBON DENGAN METODE TAGUCHI: OPTIMIZATION OF COMPOSITION PARAMETERS OF GLASS FIBER - CARBON COMPOSITES USING THE TAGUCHI METHOD - Dian Pamuji; Eli Novita (Jurnal Teknik Mesin, 2026)
The use of composite materials in electric vehicle body structures has continued to grow due to their high strength-to-weight ratio. However, the optimization of manufacturing parameters to achieve optimal mechanical performance, particularly for honeycomb-based composites, still requires further investigation. This study aims to determine the optimal combination of process parameters that maximizes the tensile strength of honeycomb-based composites for electric vehicle body applications. The parameters investigated include the fabrication method (hand lay-up and vacuum), fiber type (fiberglass, carbon fiber, and hybrid), and number of layers (4, 5, and 6 layers). The experimental design was developed using the Taguchi method with an L18 orthogonal array. The results indicate that the optimal parameter combination was achieved using the vacuum fabrication method, carbon fiber reinforcement, and six layers, resulting in the highest tensile strength of 754.56 MPa. Signal-to-noise (S/N) ratio analysis revealed that fiber type was the most influential factor, followed by the number of layers and fabrication method. Analysis of variance (ANOVA) showed that all investigated parameters had p-values below 0.05, indicating that they significantly affected the tensile strength of the composite